Cooperative Inquiry Extended: Creating Technology with Middle School Students with Learning Differences. Issue 3 (September 2013) - Foss, Elizabeth; Guha, Mona Leigh; Papadatos, Panagis; Clegg, Tamara; Yip, Jason; Walsh, Greg
Cooperative Inquiry is a method of developing technology in which children and adults are partners in the design process. Researchers use Cooperative Inquiry to empower children in the design of their own technology and to design technology that is specific to children's needs and wants. As Cooperative Inquiry is continually evolving and expanding, it is important to consider how researchers can extend this inclusive design approach to work with populations of children with disabilities. In a semester-long case study, researchers explored the use of Cooperative Inquiry in a classroom of middle school boys with learning differences, including mild to moderate autism, specific learning disabilities, and Attention Deficit Hyperactivity Disorder (ADHD). The participating class of 10 boys ages 11–12 designed a browser-based computer game using Cooperative Inquiry over the course of six design sessions. During the project, the children had overall positive experiences and were able to form partnerships with the adult researchers to develop the game. Based on the experiences of all the team members, researchers make recommendations for employing Cooperative Inquiry in special education classrooms. These include adding informal time during the design sessions, maintaining a high adult-to-child ratio, giving instructions using many modalities, and planning for high engagement. Through this work, researchers broaden Cooperative Inquiry's applicability to a new population in a classroom setting, and provide guidance for designing with populations of children with special leaning needs in the future.